Challenges and Opportunities in the Power Sector Reform of Abuja Electricity Distribution Company - Muhammad, Isa; Aliegba , Eugene T.; Baban’umma, Mohammed Bello (Kashere Journal of Politics and International Relations, 2024)
Nigeria Power sector reform was performed between the year 2010 and 2013 but has undoubtedly been adjudged unsuccessful by most stakeholders. The failure of the reform is evidenced by a myriad of seemingly insurmountable economic, institutional, technical, financial and socio-political challenges exacerbated by the recent macroeconomic crisis. This study examined challenges and opportunities in the power sector reform of Abuja electricity distribution company with a sample size of 251 determined using the Raosoft calculator. Data collection utilized a self-structured questionnaire, and analysis employed descriptive statistics like frequency count and mean. The findings showed power sector reform in Abuja Electricity Distribution Company (AEDC) has revealed challenges related to poor funding, inadequate implementation of reforms, and a lack of essential infrastructure. The study recommends prompt, continuous and effective stakeholders’ engagement is critical at the states, local government and communities to resolve the socio-political and conflict of interest issues such as the tariff design, gas pipeline vandalization.